Development of IT-Based Card Media on the Digestive System Topic to Improve Students’ Critical Thinking Skills and Learning Activities - Nurulul Fatimah; Joko Sulianto; Fenny Roshayanti (FKIP - Universitas Riau, 2026)
Integrated Science and Social Studies (IPAS) learning in primary education aims to prepare students to face future challenges through active learning activities. Critical thinking skills play a crucial role in enabling students to evaluate ideas and actively engage in the learning process. This study aimed to develop IT-based card media for digestive system material that is valid, practical, and effective in improving students’ critical thinking skills and learning activities. The research employed a Research and Development approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The participants were 19 fifth-grade students of Pandeanlamper 02 Elementary School, Semarang, selected through purposive sampling. The results of expert validation by media experts, material experts, and practitioners indicated that the developed media met the criteria of very valid. Furthermore, the implementation of the IT-based card media showed an improvement in students’ critical thinking skills and learning activities after its use. Overall, these findings suggest that IT-based card media is feasible and effective as a learning medium to support the development of critical thinking skills and active learning in primary education.